2021
DOI: 10.1177/00034894211059599
|View full text |Cite
|
Sign up to set email alerts
|

ASA Physical Status Classification and Complications Following Facial Fracture Repair

Abstract: Background: To investigate the association between American Society of Anesthesiologists (ASA) physical status classification and rates of postoperative complications in patients undergoing facial fracture repair. Methods: Patients were divided into 2 cohorts based on the ASA classification system: Class I/II and Class III/IV. Chi-square and Fisher’s exact tests were used for univariate analyses. Multivariate logistic regressions were used to assess the independent associations of covariates on postoperative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
4
2
Order By: Relevance
“…15 A 2021 study demonstrated that ASA classes III/IV was associated with increased DWI, postoperative bleeding, and failure to wean off the ventilator. 16 The authors did not demonstrate the association between ASA class and readmission or return to OR in multivariate analyses as we observed in this study. A similar study conducted in 2017 also reported a correlation between ASA Class III/IV and postoperative wound infection following facial fracture repair.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…15 A 2021 study demonstrated that ASA classes III/IV was associated with increased DWI, postoperative bleeding, and failure to wean off the ventilator. 16 The authors did not demonstrate the association between ASA class and readmission or return to OR in multivariate analyses as we observed in this study. A similar study conducted in 2017 also reported a correlation between ASA Class III/IV and postoperative wound infection following facial fracture repair.…”
Section: Discussioncontrasting
confidence: 77%
“…For facial fracture repair specifically, increased ASA classification has been associated with a variety of postoperative complications 15 . A 2021 study demonstrated that ASA classes III/IV was associated with increased DWI, postoperative bleeding, and failure to wean off the ventilator 16 . The authors did not demonstrate the association between ASA class and readmission or return to OR in multivariate analyses as we observed in this study.…”
Section: Discussioncontrasting
confidence: 52%
“…Previous studies have shown higher ASA status to be associated with poorer outcomes in a variety of procedures, ranging from spinal surgery to facial fracture repair. [24][25][26] The most relevant study in which an increased ASA status was predictive of poor outcomes was performed by Goobie and colleagues. 27 In their study, which looked at pediatric patients undergoing complex cranial vault reconstruction, they found that an ASA status of 3 or 4 and craniofacial syndromes were predictive of poorer outcomes and could effectively assist in risk stratifying patients.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were as follows: (1) Age ≥ 65 years; (2) Pelvic fracture caused by low-energy injuries, such as falling from a standing position; (3) Treated with minimally invasive repositioning and fixation or conservative treatment; (4) Complete clinical data and (5) Follow-up time > one year. The exclusion criteria included (1) younger patients with a high-energy trauma; (2) pathological fractures, such as metastatic tumours, fractures caused by high doses of hormones and open fractures; (3) incomplete clinical and follow-up data; (4) those with less than one year of post-operative follow-up; (5) patients who died during the follow-up period; and (6) those with ASA classification IV or above [ 13 ]. Informed consent was obtained from all included patients.…”
Section: Methodsmentioning
confidence: 99%
“…General information about the patients, including sex, age, duration of illness, cause of injury, AO/OTA classification [ 13 ], low body mass index (BMI) [ 15 ], bone mineral density, time to admission owing to injury, ASA classification and underlying disease, of the patients were recorded before surgery. The mean time in bed, clinical fracture healing, and VAS [ 16 ] and Majeed functional scores [ 17 ] were compared.…”
Section: Methodsmentioning
confidence: 99%